تحديد المحتوى من الميتانول في بعض المشروبات الكحولية (النبيذ والعرق) المحضرة بالطرق المحلية التقليدية - الخير, معروف; ياسين, مفيد; معروف, هلا (Latakia University Journal -Medical Sciences Series, 2017)
يعد العرق والنبيذ من المشروبات الكحولية شائعة التناول في سورية، غير أن هذه المشروبات غالباً ما تنتج دون مراقبة لدورة التصنيع من حيث التخمير والتقطير، مما يعرض متناوليها لخطر التسمم بمادة الميتانول, وهذا ما يؤكد ضرورة إخضاع إنتاجها للمراقبة الشديدة. يهدف هذا البحث إلى تحديد تركيز الميتانول في المشروبات الكحولية النبيذ والعرق المحضرة بالطرق المحلية التقليدية، والتحقق من مطابقتها للمواصفة القياسية السورية. حيث تم تحليل العينات باستخدام الطريقة اللونية (كطريقة مرجعية) التي تعتمد على القياس بمجال الأشعة المرئية عند طول موجة (575 nm) باستخدام مقياس الطيف الضوئي ((spectrophotometer، ثم تمت مقارنة النتائج مع المواصفة القياسية السورية رقم /2478/ لعام /2003/، حيث تم اختبار 50 عينة من النبيذ والعرق المحضرة بالطرق المحلية التقليدية. أظهرت هذه الدراسة التباين في تركيز الميتانول، كما أظهرت ضرورة تطبيق نظام مراقبة لتوفير جودة هذا المشروبات الشعبية. The Arak and Wine are common alcoholic spirits in Syria. However, those spirits are often produced outside the controls of the manufacturing cycle in terms of fermentation and distillation, thus exposing the consumers to risk of methanol poisoning, which confirms the need to submit their production to the control as extremely essential. The aim of this study to determination of methanol in some alcoholic beverage prepared by traditional local methods in order to verify conformity of local Alcohol Syrian standard specification. The samples were tested by using colorimetric method as official methods depending on the measurement using spectrophotometer at (575 nm).In comperation with the standard Syrian specifications number /2478/ year (2003), there were fifty test samples (Arak and Wine) collected from locally available. The study showed the amount of variation in the concentration of methanol depending on the difference in the method of preparation fermenting grapes. furthermore the importance of applying the control system to provide the quality of those popular spirits.